Hubungan Pengetahuan dan Status Gizi Ibu Hamil Terhadap Kejadian Anemia di Klinik Sari Mutiara Tandem Kabupaten Deli Serdang Tahun 2023 - Diah Safitri; Erin Padilla Siregar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
If anemia during pregnancy is not treated, it can cause serious consequences, namely bleeding. Bleeding is the main cause of the high maternal mortality rate (MMR) in Indonesia. nutrition on the incidence of anemia at the Sari Mutiara Tandem Clinic, Deli Serdang Regency in 2023. Anemia is a condition where blood hemoglobin levels are below normal. The cause is a lack of blood-forming substances, such as a lack of iron, folic acid or vitamin B12. Iron anemia or what is called Iron Nutritional Anemia (AGB) often occurs in mothers. This research uses a quantitative type of research using retrospective research. This research design was carried out using a cross sectional approach, the sample was all 35 pregnant women. Research Results: 17 pregnant women who had good knowledge and did not experience anemia (94.4%). And Pregnant Women with less knowledge and experiencing anemia were 14 people with a percentage of (82.4%) Statistical Test Results obtained p value = 0.033<0.05 which means there is a relationship between Nutritional Status and the incidence of anemia in Pregnant Women. It is hoped that for pregnant women to increase knowledge about anemia, especially regarding methods and efforts to prevent anemia, and continuously monitor nutritional status.